Pharmacokinetics and tolerance of dehydroandrographolide succinate injection after intravenous administration in healthy Chinese volunteers - Chen Qian; Liu Yun; Liu Yan-mei; Liu Gang-yi; Zhang Meng-qi; Jia Jing-ying; Lu Chuan; Yu Chen (Acta Pharmacologica Sinica, 2016)
Aim: Dehydroandrographolide succinate (DAS) is extracted from herbal medicine Andrographis paniculata (Burm f) Nees. DAS injection is used in China for the treatment of viral pneumonia and upper respiratory tract infections. The aim of this study is to investigate the pharmacokinetics and tolerance of DAS injection in healthy Chinese volunteers. Methods: This was a single-center, randomized, single-dose, three-way crossover design study. Nine eligible subjects were randomly divided into 3 groups, and each group sequentially received 80, 160, or 320 mg of DAS infusion according to a three-way Latin square design. Plasma and urine samples were collected and determined using an LC-MS/MS method. Safety and tolerability were determined via clinical evaluation and adverse event monitoring. Results: For the 80, 160, and 320 mg dose groups, the mean Cmax were 4.82, 12.85, and 26.90 mg/L, respectively, and the mean AUC0–12 were 6.18, 16.95, and 40.65 mg·L−1·h, respectively. DAS was rapidly cleared, with a mean Tmax of 0.94–1.0 h and a t1/2 of approximately 1.51–1.89 h. Approximately 10.1%–15.5% of the intravenous DAS dose was excreted unchanged in urine within 24 h in the 3 groups, and more than 90% of unchanged DAS was excreted between 0 and 4 h. The pharmacokinetic profile was similar between male and female subjects. No serious or unexpected adverse events were found during the study, but one mild adverse event (stomachache) was reported. Conclusion: This study shows that DAS has nonlinear pharmacokinetic characteristics. To guarantee the effective concentration, mul¬tiple small doses are recommended in clinical regimens.